(untitled) (Journal of history, 2023)
In the 12th-13th centuries, medieval Italian states were considered as very active players in international relations. During this period, the Italian states carried out huge political processes in the Mediterranean, South-Eastern Europe and the Middle East. Also, the Italian states established political, social, trade and economic relations with the greatest empire in the steppes of Eurasia, the Golden Horde. This is evidenced by many sources in Italian. This scholarly article examines the different relationships between the Golden Horde and the medieval Italian states based on Italian sources. The history of the relationship between the Golden Horde and the Vatican, Venice, Genoa, and Florence is also explored. One of the main objectives of the scientific article is to determine the level of relations between Italians and the Golden Horde and other Mongol uluses. The article also analyzes the regional policy of Italian states, strategy and goals.